Sistem Informasi Pendataan Penduduk Tingkat Kecamatan Pada Kantor Kecamatan Pringkuku Kabupaten Pacitan - Anggraeni, Defi; Purnama, Bambang Eka; ., Sukadi (Speed - Indonesian Journal on Computer Science, 2014)
ABSTRACT : System logging information at the level of District residents are typically still use conventional systems. This has led to some fairly troublesome barriers, particularly on ketidakvalidan and a mismatch of data. Also occurs when constraints on information retrieval about a new resident, or resident who moved from the District. So it is with the provision of the data, for example data job, educational data, demographic data and population that is often not up to date. Departing from the above constraints, the harsher draft a population information system. System logging information resident on this Subdistrict levels will greatly assist government agencies in conducting logging inhabitants in scope in district. Where the system is going to do the logging process in line with the process of filing papers on population by every resident who came to the Office of the District. Thus population data can be obtained easily without having to perform logging directly to where the people live.The system is built is designed with grooves and a simple interface design, so that it can be easily used in dilingkup Sub-district Office. Keywords: information systems, Logging, population ABSTRAKSI : Kecamatan Pringkuku merupakan suatu instansi pemerintah yang menangani semua data-data penduduk dalam wilayah Kecamatan Pringkuku yang mempunyai informasi data-data penduduk yang dibutuhkan oleh penduduk Kecamatan Pringkuku, maupun instansi pemerintah yang lebih tinggi. Saat ini Kecamatan Pringkuku menangani semua data kependudukan dengan cara yang kurang relevan seperti penyajian laporan yang tidak tepat waktu. Pengolahan data penduduk di Kecamatan Pringkuku merupakan tugas pokok dan fungsi dari bidang Pemerintahan. Tapi dalam menangani proses laporan pendataan penduduk tersebut masih bersifat konvensional sehingga menyebabkan staf yang bertugas mengalami kesulitan dalam menangani laporan data kependudukan tersebut. Penelitian ini bertujuan untuk menghasilkan sebuah Sistem informasi pendataan penduduk dengan menggunakan java danÂ  MySQL. Dalam penelitian ini selain memaparkan kajian teori yang digunakan sebagai dasar penyusunan, juga akan membahas mengenai wawancara , analisis, perancangan sistem, dan implementasi sistem. Dengan adanya sistem pengolahan data penduduk ini diharapkan dapat menghasilkan laporan data kependudukan yang akurat, efektif dan efisien. Kata kunci : Sistem Informasi, Pendataan, Kependudukan